Well said intro : - Grant, Linda (Thomson/Heinle, 2007)
Offering a lively and communicative approach for increasing pronunciation and speaking skills, Well Said Intro provides beginning to mid-intermediate students with the pronunciation and speaking tools they need to communicate in social, academic, and professional settings.